The effects of in-process cooling during friction stir welding of 7475 aluminium alloy - Jacob, Ashish; Maheshwari, Sachin; Siddiquee, Arshad Noor; Al-Ahmari, Abdulrahman; Abidi, Mustufa Haider; Konovalov, Sergey; Chen, Xizhang (Penerbit Universiti Kebangsaan Malaysia, 2021)
Certain age hardenable alloys such as AA7475 cannot be joined with perfection using fusion welding techniques. This requires non-conventional welding technique such as friction stir welding process to join these ‘difficult to weld’ alloys. In this study, three different cooling conditions i.e. cryogenic, sub-zero, and zero-degree Celsius temperature conditions have been analyzed to understand its impact on the welding process. In-process cooling was found to behave effectively and also enhanced the mechanical properties of the welded joints. A stable microstructure was clearly seen in the images observed under the metallurgical microscope. The weld efficiencies were found to be good in each of the samples which are indicative of a strong metallic joint. The effective cooling conditions employed had an overall positive impact on the joint.